2013
DOI: 10.1111/ijcp.12194
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron for the treatment of overactive bladder: a prespecified pooled efficacy analysis and pooled safety analysis of three randomised, double‐blind, placebo‐controlled, phase III studies

Abstract: IntroductionTo examine pooled efficacy data from three, large phase III studies comparing mirabegron (50 and 100 mg) with placebo, and pooled safety data including additional mirabegron 25 mg and tolterodine extended release (ER) 4 mg results.MethodsThis prespecified pooled analysis of three randomised, double-blind, placebo-controlled, 12-week studies, evaluated efficacy and safety of once-daily mirabegron 25 mg (safety analysis), 50 or 100 mg (efficacy and safety analyses) and tolterodine ER 4 mg (safety ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
172
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(189 citation statements)
references
References 38 publications
14
172
3
Order By: Relevance
“…Both classes of drugs exhibit similar efficacy, but unlike antimuscarinics, mirabegron is not associated with anticholinergic side effects. [10][11][12] Patients are usually initiated on an antimuscarinic, with dose escalation if symptom improvement is inadequate. This may increase the anticholinergic burden, the risk of bothersome side effects and treatment discontinuation.…”
mentioning
confidence: 99%
“…Both classes of drugs exhibit similar efficacy, but unlike antimuscarinics, mirabegron is not associated with anticholinergic side effects. [10][11][12] Patients are usually initiated on an antimuscarinic, with dose escalation if symptom improvement is inadequate. This may increase the anticholinergic burden, the risk of bothersome side effects and treatment discontinuation.…”
mentioning
confidence: 99%
“…13 The mean number of micturition episodes also decreased significantly with mirabegron 50mg compared to placebo, -1.75 versus -1.20 respectively (p<0.05).…”
Section: Trends In Urology and Men's Health September/october 2016mentioning
confidence: 87%
“…27 In a pre-specified pooled analysis of three 12-week, randomized, placebo-controlled studies (one of which also included a tolterodine ER 4 mg arm), mirabegron (50 mg and 100 mg once-daily) was associated with statistically significant reductions in incontinence episodes, frequency, and urgency compared with placebo. 28 The pooled analysis included an active-controlled study (SCORPIO), designed to compare the efficacy between mirabegron and placebo, as well as tolterodine ER (4 mg once-daily; included as an active control to placebo). The study, showed statistically significant reductions in incontinence episodes and micturition frequency (the co-primary endpoints) for mirabegron vs. placebo, but not for tolterodine ER 4 mg vs. placebo.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42]48 Unit costs per incontin- Symptom severity cutoff points between different levels were roughly based on qui ntiles for each number in pooled data from three pivotal, randomized trials of mirabegron: SCORPIO, 29,31 ARIES, 28 and CAPRICORN. 37 Patient distribution was based on the SCORPIO study.…”
mentioning
confidence: 99%
See 1 more Smart Citation